Overview of the Capital Markets in Vietnam and Directions for Development - World Bank (Washington, DC, 2013)
The World Bank undertook a study project on Vietnam s capital markets and sent a mission to Vietnam from May 15 to May 27, 2005. This report is the result of the study project. The objectives of the project were to review, analyze and evaluate the situation of Vietnam s securities markets vis-a-vis experiences of other developing countries, including transition economies; to work with the officials of the State Security Commission of Vietnam (SSC), to make specific recommendations for a five-year plan of Vietnamese capital market development in light of policy implementation sequence and priorities; to make suggestions on the draft of the Action Plan for Securities Market Development for the period of 2006-2010 and comment on the Prime Minister's Decision No 163 on the Strategy for the Development of Vietnam's Securities Market up to year 2010; and to identify desirable capital market-related projects and programs to be administered by the Bank in line with Vietnam's overall economic development strategy. This report is organized as follows: Sections 2 and 3 will overview Vietnam's macroeconomic situation and the financial markets in Vietnam. Section 4 will examine SOE equitization, foreign direct investments, and private sector development. Section 5 will review the operation of Vietnam s capital markets in terms of their regulatory framework and activities. Section 6 will explore two principal impediments to Vietnam's capital market development, namely its nascent government securities market and its inactive primary market. Section 7 will discuss the policy and institutional problems that have been adversely affecting the whole financial sector in Vietnam. Finally, Section 8 will recommend policy actions to be implemented under the five-year plan of Vietnamese capital market development.